STRATEGI PEMASARAN DALAM MEMBANTU MENINGKATKAN PENJUALAN MELALUI MEDIA SOSIAL DI PT.SURYA LIFETIME - Nugroho Sumedi; Ahmad Taufik At (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This article is a qualitative research that aims to answer the problems that occur at PT. Surya Lifetime Surabaya, and the method used for this research is descriptive qualitative. Which is where this research collects data by way of observation, interviews and documentation to find out marketing strategies in helping increase sales through social media at PT. Surya Lifetime. From this research, we obtained recommendations for input materials to the company PT. Surya Lifetime, namely by expanding market segmentation again and creating a more effective strategy to help increase company profitability.